Somewhere between Malmö and Copenhagen: Inter-spaces in Marius Ivaškevičius’ play Close City - Räthel, Clemens (Folia Scandinavica Posnaniensia, 2023)
In the drama Close City, first published in 2005, Lithuanian playwright Marius Ivaškevičius focuses on the (im)possible connections between Malmö and Copenhagen. The initially realistic setting of a failing marriage in the spirit of August Strindberg and Ingmar Bergman evolves gradually into an absurd spectacle that explores spatial and intertextual interstices. This article investigates how the drama, as a scenic kaleidoscope, elaborates on the influence of imagined geographies in the Baltic Sea region, discusses (gendered) power relations, and questions Scandinavian exceptionalism.